Understanding international long-term interest rate comovement - Michael Chin; Ferre De Graeve; Thomai Filippeli; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2018)
Long-term interest rates of small open economies correlate strongly with the US long-term rate. Can central banks in those countries decouple from the US? An estimated DSGE model for the UK (vis-`a-vis the US) establishes three structural empirical results. (1) Comovement arises due to nominal fluctuations, not through real rates or term premia. (2) The cause of comovement is the central bank of the small open economy accommodating foreign inflation trends, rather than systematically curbing them. (3) Small open economies may find themselves much more affected by changes in US inflation trends than the US itself.
Keywords: E43; E44; F30; F44; F65; G15; 330; DSGE Model; Small Open Economy; Yield Curve; Long-Term Interest Rates; Term Premia; Comovement